Konsep dan Teori Kurikulum PAI di Sekolah dan Madrasah - Zulkifli, Zulkifli; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Jurnal Ilmiah Global Education, 2024)
Islamic Religious Education (PAI) plays an important role in shaping the character of Indonesian students, both in public schools and madrasahs. The goal of the PAI curriculum is to form students who are obedient and respectful to Allah SWT and are able to apply Islamic principles in everyday life. This article discusses the concepts and theories that support the development of the PAI curriculum, such as constructivism, perennialism, essentialism, and progressivism. In addition, this article discusses the implementation of the PAI curriculum in schools and madrasahs, as well as the challenges and solutions in the field. The research findings show that, although there are differences in the way the PAI curriculum is implemented in schools and madrasahs, both have the same goal, namely to form noble students. The main considerations in developing the PAI curriculum are teacher quality, curriculum standards, and the integration of Islamic principles. The solutions used include.